Photochemical Degradation of Hyperforin - D'Auria, Maurizio; Emanuele, Lucia; Racioppi, Rocco (Letters in Organic Chemistry, 2008)
Irradiation of hyperforin in acetonitrile gave a single degradation product with a first order kinetics (k = 3.23 M h-1). The degradation product was a 1:1 tautomeric mixture of 2-methyl-3-hydroxy-4-(1-oxo-2-methyl-1-propyl)-1,5- dioxo-6-(3methyl-1-but-2-enyl)-2-cyclohexene and 2-methyl-1,3,5-trioxo-4-(1-hydroxy-2-methyl-1-propylene)-6-(3-methyl- 1-but-2-enyl)-cyclohexane. The product can also be obtained through three Norrish II reactions, followed by a fragmentation reaction.
Keywords: fragmentation reaction